Evaluation of performance and genetic parameters in quality protein maize genotypes - Regmi, Aradhana; Niraula, Dikshya; Shrestha, Upasana; Shrestha, Suraj; Kandel, Bishnu Prasad (Journal of Agriculture and Natural Resources, 2022)
Quality protein maize (QPM) contains opaque-2 mutant genes that increases lysine and tryptophan level which are not normally found in maize. The objective of this study was to evaluate the performance of QPM genotype based on their yield, yield attributing and other relevant characteristics. A varietal trial on QPM was conducted in the research field of Lamahi municipality-3, Dang, Nepal from February to June 2021. This experiment was performed in Randomized Complete Block Design with three replications. Thirteen genotypes of QPM and one standard check (Poshilo Makai-2) were evaluated. Each genotype was assigned an area of 3m × 3m with a net plot area of 452.5m2 per block. Analysis of variance revealed significant data for the most of the genotypes. Four genotypes Rampur-S13FQ-02 Rampur-SO3FQ-02, Rampur-S13FQ010 and Rampur-S13FQ-08 were found superior with a yield of 4.32 t/ha, 3.97 t/ha, 3.89 t/ha, 3.63 t/ha respectively in comparison to the standard check Poshilo makai-2 (2.66 t/ha). Significant and positive correlation were observed for the ear length, ear diameter, number of kernels per ear, number of kernel row per ear, ear weight whereas negative for ear aspect with grain yield was observed. Ear weight without husk had the highest contribution to grain yield. For all observed traits, the coefficient of phenotypic variation (PCV) was found to be higher than that of genotypic coefficient of variation (GCV). The highest GCV, PCV, genetic advance and heritability were observed in ear aspect, thousand grain weight, ear height, plant height respectively. As a result, breeding programs can be further improved by selecting these traits.